Pitfalls in Genetic Testing for Consanguineous Pediatric Populations - Maha Saleh; Samantha Colaiacovo; Melanie P. Napier; Asuri N. Prasad; C. Anthony Rupar; Chitra Prasad (Case Reports in Genetics)
We describe the diagnostic odyssey of an eight-year-old female born to consanguineous parents. Our patient presented with global developmental delay, regression, microcephaly, spastic diplegia, and leukodystrophy confirmed on brain magnetic resonance imaging (MRI). She was found on whole exome sequencing (WES) to have dual genetic diagnoses. The first was a homozygous pathogenic HERC2 gene partial deletion of exons 43–45 that causes HERC2-related disorder. The second was a homozygous pathogenic variant (c.836 C > T, p.A279 V) in the SUMF1 gene responsible for multiple sulfatase deficiency. This case highlights some of the challenges in diagnosing consanguineous pediatric populations where standard genetic and metabolic testing may not provide answers. Our case further supports the recent American College of Medical Genetics and Genomics (ACMG) recommendation of WES as a first or second-tier test for patients with developmental delay, particularly in a population where the chances of dual diagnosis is high.